Curriculum planning and classroom environment in natural sciences: from policies and guidelines to institutional application - Hernández-Suárez, César Augusto; Avendaño-Castro, William Rodrigo; Rojas-Guevara, Jorge Ulises (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Quality in education requires a complete articulation between educational policies and what is done in the classrooms. The objective of the study is to analyze these two factors, applied within the area of natural sciences of a Colombian educational institution, for the levels of basic and secondary education. It is a qualitative research, descriptive level, in which the hermeneutical method and categorization were used. Three teachers of natural sciences and environmental education participated in the study, to whom a categorization matrix was applied on their subject and classroom planning, as well as on national policies. In politics, the most relevant category is scientific competence, associated with the ability to carry out scientific research. However, from the curricular planning and the classroom environment, little goes into the skills of this competence. It is concluded that the curricular planning of the teachers and the classroom environment do not conform to the educational policies, in relation to the teaching of natural sciences.